Primary Hyperparathyroidism Due to Parathyroid Adenoma: Clinical Case - A. E. Shklyaev; A. M. Khisamutdinova; A. G. Bessonov; O. V. Muravtseva; A. V. Kobelev; S. N. Styazhkina (Архивъ внутренней медицины, 2021)
Primary hyperparathyroidism (PGPT) is an endocrine disease characterized by excessive secretion of parathyroid hormone (PTH) in upper — normal or elevated blood calcium levels due to primary parathyroid gland pathology (osch). Primary hyperparathyrosis, depending on the clinical manifestations, can occur in the normocalcemic, mild and manifest form. This article presents a clinical case of the development of the manifest form by the type of visceral disorders. Which appeared in the form of pathology of the gastrointestinal tract. This form of the disease is an indication for surgical treatment and further correction of calcium-phosphorus metabolism.